Rapid Serodiagnostics for Plant Disease Identification and Management-Lateral Flow Assay - Suresh, M.; Madhavi, G. Bindu; Roja, V. (Chronicle of Bioresource Management, 2021)
Detection is the best protection and disease diagnosis plays an important factor in crop protection and management of the plant diseases. Among the different diagnostic tests for plant pathogens, serological based Lateral Flow Assay (LFA) was very widely adopted due to its simple use coupled with high sensitivity. In the recent past, several LFAs were developed for rapid diagnosis of several plant pathogens including, fungi, bacteria and viruses, across the globe.